The Effects of Chronic Cortisol Elevation on Thermal Tolerance in Zebrafish (Danio rerio) - Orsar, Albrightine (Université d'Ottawa / University of Ottawa, 2025)
The present study tested whether chronic cortisol elevation influences thermal tolerance in zebrafish (Danio rerio), a species living near its upper thermal limit. Four days of cortisol treatment reduced CT_max by ~1°C, an effect that was alleviated once cortisol returned to baseline. Using glucocorticoid receptor (GR) and mineralocorticoid receptor (MR) knockout fish, as well as the GR antagonist RU486, revealed that the GR was the key mediator of cortisol’s action on CT_max. To probe the mechanisms underlying this effect, temperature-sensing proteins (thermoTRPs) were examined. Blockade of TRPV1 using capsazepine, increased CT_max, and cortisol treatment elevated trpv4 splice variant 3 transcripts in gill tissue, suggesting that cortisol's effects on CT_max may be mediated by changes in temperature sensing. Cortisol treatment during early development (0–5 days post-fertilization) produced adults with lower CT_max values than vehicle-treated control fish, suggesting that cortisol in early development has programming effects on thermal tolerance. Overall, our findings reveal that elevated cortisol, and by extension chronic stress, compromises thermal tolerance in zebrafish, with implications for fish health under climate warming.
Keywords: zebrafish; thermal tolerance; cortisol; anthropogenic factors; global warming